Federal Government Capital Expenditure and Its Impact on Nepalese Economy - Agrawal, Salu Kumari; Lertjanyakit, Hatairat (Nepalese Journal of Management Science and Research, 2019)
This paper examines the effect of government capital expenditure on Nepalese economy over a period from 1974/75 to 2015/16. Agriculture, Health, Transportation, Electricity and Education are independent variables whereas, economic growth is dependent variable. Data are collected from the website of NRB (Financial Statistics Report). The study is based on 43 samples. The regression models are estimated to test the significant and importance of government expenditure and its impact on economy in Nepal. The result shows that there is positive correlation between agriculture, health, transportation, electricity, education and economic growth. The result shows that beta coefficient is positive for agriculture, health, transportation, electricity, education and economic growth.